Ethnomathematical Exploration Of Somba Opu Fort In Gowa, South Sulawesi - Andi Kusumayanti,; Sitti Nur Alisyah Saputri,; Sri Zuhrianugrah,; Syarifuddin, Andi Alfian; Andi Eritme Yustika Abrar, (Alauddin Journal of Mathematics Education, 2024)
Somba Opu Fortress, located in Gowa, South Sulawesi, is a historical site with a significant role in the history of the Gowa-Tallo Kingdom. The construction and architectural design of this structure reflect geometric elements, providing an opportunity to explore the concept of ethnomathematics. This research aims to delve into ethnomathematical concepts at Somba Opu Fortress and understand their connection to mathematics learning, particularly in the field of geometry.The research employs an ethnographic approach with qualitative descriptive research. The study is conducted at Somba Opu Fortress in Gowa, South Sulawesi. Data is collected through observation, interviews, and documentation. The results indicate that the fortress exhibits striking geometric structures, including elements such as squares, triangles, circles, and parallelograms. The roofs of the buildings resemble triangles and rectangular pyramids, while the fortress walls contain geometric elements with variations in materials. The study highlights the rich ethnomathematical aspects of Somba Opu Fortress and their relevance to the broader context of mathematics education, specifically within the realm of geometry.